Fear of Missing Out (FoMO) and Its Correlation with Mental Health of Saraswati 1 Denpasar High School Students - I Nyoman Gede Semarajana; Anak Agung Dwi Ratih Arningsih; I Gede Jenstin Prana Arsana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research explores the relationship between Fear of Missing Out (FoMO) and mental health among high school students at Saraswati 1 Denpasar High School, Bali. Employing a cross-sectional quantitative approach, the study assessed FoMO levels using the FoMO Scale by Przybylski et al., and mental health aspects—depression, anxiety, and stress—using the DASS-21 scale. A total of 236 students, selected through convenience sampling, participated in the study, with data analyzed using descriptive and correlation tests. The findings indicate that 40.7% of students experienced moderate levels of FoMO, while significant proportions reported severe or very severe anxiety (38.1%) and stress (37.3%). Correlation analyses using Spearman and Pearson tests revealed positive and significant relationships between FoMO and depression (r = 0.322, p < 0.01), anxiety (r = 0.361, p < 0.01), and stress (r = 0.404, p < 0.01). These results emphasize the influence of excessive social media use on adolescents' mental health, highlighting the importance of interventions like counseling and educational programs to address FoMO's psychological effects. The study's limitations include sampling constraints and absenteeism, indicating the need for future research with more comprehensive methods.